The LapG protein plays a role in Pseudomonas aeruginosa biofilm formation by controlling the presence of the CdrA adhesin on the cell surface - Rybtke, Morten (2016)
Pseudomonas aeruginosa is a clinically relevant species involved in biofilm-based chronic infections. We provide evidence that the P. aeruginosa LapG protein functions as a periplasmic protease that can cleave the protein adhesin CdrA off the cell surface, and thereby plays a role in biofilm formation and biofilm dispersal. The P. aeruginosa LapG protein is shown to be a functional homolog of the Pseudomonas putida LapG protein which has previously been shown to function as a periplasmic protease that targets the surface adhesin LapA. Transposon mutagenesis and characterization of defined knockout mutants provided evidence that the CdrA adhesin is a target of LapG in P. aeruginosa. A wspF lapG double mutant was hyper-aggregating and hyper biofilm forming, whereas a wspF lapG cdrA triple mutant lost these phenotypes. In addition, western blot detection of CdrA in culture supernatants and whole-cell protein fractions showed that CdrA was retained in the whole-cell protein fraction when LapG was absent, whereas it was found in the culture supernatant when LapG was present. The finding that CdrA is a target of LapG in P. aeruginosa is surprising because CdrA has no homology to LapA.